Post-marketing safety of lorlatinib: a real-world study based on the FDA adverse event reporting system - Li, Huqun; Wang, Chongshu; Guo, Cuilian (Frontiers in Pharmacology, 2024)
Background: Lorlatinib displays marked systemic and intracranial efficacy against anaplastic lymphoma kinase (ALK) positive non-small cell lung cancer (NSCLC). We aimed to establish the safety profile of lorlatinib based on the Food and Drug Administration Adverse Event Reporting System (FAERS).Methods: Reports from the FAERS between 2019 and 2023 were collected to conduct the disproportionality analysis. Reporting odds ratio (ROR) was employed to detect the potential adverse events (AEs) related to lorlatinib. The clinical characteristics, age and gender differences, time to onset of AEs were also investigated.Results: A total of 2,941 AE reports were found to be associated with lorlatinib among the 8,818,870 AE reports obtained from the FAERS database. 167 lorlatinib-related AE signals were identified. The frequently reported AEs including hypercholesterolemia, oedema, and cognitive disorder were in line with those observed in clinical trials and drug instruction. However, AEs such as interstitial lung disease and AV block indicated in the drug label require further evaluation. More attention should be paid to the new potential unexpected AEs including pulmonary arterial hypertension and radiation necrosis. Furthermore, we examined the specific high-risk AEs of different ages and genders. In addition, majority of AEs occurred within the first 2 month after lorlatinib initiation with a median onset time of 51 days.Our study provides valuable insight into the post-marketing safety profile of lorlatinib, which can potentially benefit the rational and safe administration of lorlatinib in the clinic. Further prospective studies are needed to validate the associations between lorlatinib and the identified AEs.